Solution of Two Linear Equation Singularly Perturbed of First Order PDE on Argument (Journal of University of Babylon for Engineering Sciences, 2017)
Two systems of linear singularly perturbed problems in first order partial derivatives were considered. This system depends on a small parameter, and the small parameter exists in the left and right hands of it. Also, we prove the uniqueness of this  solution  is uniform  in  the  space  and asymptotic approximation of any rank was constructed.